The Oldest Vocation : Christian Motherhood in the Medieval West - Atkinson, Clarissa W. (Cornell University Press, 2019)
From the myth of Joan to the experiences of saints, nuns, and ordinary women, The Oldest Vocation brings to life both the richness and the troubling contradictions of Christian motherhood in medieval Europe.